Pengaruh Lingkungan Keluarga Terhadap Keataan Pada Tatatertib Siswa Sekolah Dasar - Katrina Siwi (Peneliti.net, 2022)
The purpose of this study was to determine whether the Family Environment Affects the Compliance with Student Disciplines at the State Elementary School II Tomohon, Matani District, Central Tomohon, and to find out how much the Family Environment Affects the Compliance with the Student Disciplines at the State Elementary School II Tomohon, Matani, Central Tomohon District. In this study, the data collection methods used were: the questionnaire method (questionnaire). The questionnaire in this study consisted of questions that were used to collect data related to social competence variables. The school environment at State Elementary School II Tomohon has been well implemented in supporting the teaching and learning system. The implementation of teacher professionalism at State Elementary School II Tomohon is still quite good. Teacher professionalism has a low or no relationship with the creation of a good school environment. The influence of teacher professionalism on the school environment at State Elementary School II Tomohon is significant and linear, so that the better the professionalism of the teacher, the better the school environment.